Bentuk, Fungsi, dan Makna Minuman Alkohol Tradisional dalam Prasasti Masahar Abad 10 Masehi - Fatihah, Lauhil; Riyanto, Edi Dwi (Jurnal Artefak, 2025)
Traditional alcoholic beverages are one of the culinary delights that have existed since the Ancient Javanese period, one of the proofs of the existence of these beverages is in the Masahar Inscription. The Masahar Inscription is an inscription issued by Mpu Sindhok in the 10th century AD for the inauguration of the sima land, namely Masahar. The inscription mentions three traditional alcoholic beverages, namely siddhu, cinca, and tuak. This study aims to determine the form, function, and meaning of traditional alcoholic beverages in the 10th century AD Masahar Inscription. This research is qualitative research through a case study approach. Data collection techniques, namely observation, interviews, and documentation. The study used interpretive qualitative with an analysis model of form, function, and meaning. The results of the study indicate that traditional alcoholic beverages mentioned in the Masahar Inscription are alcoholic beverages that are not only interpreted profanely, but also have sacred functions that are carried out in special ways according to the practices of ideology, politics, religion, social and culture that prevailed during the Ancient Javanese period. The study contributes to the preservation of intangible cultural heritage, especially the tradition of making and using traditional alcoholic beverages that may still exist or have changed form until now. Interdisciplinary research that combines historical, archaeological, and cultural anthropological methods is highly recommended to explore the symbolic and ritual aspects of alcoholic beverages in social and religious contexts.